Innovative Activities in the Field of Hotel Business and Tourism - TLESOVA, Aigul; PRIMBETOVA, Saule; SULTANOVA, Menslu; YESSENGALIYEVA, Saltanat; YERZHANOVA, Zhanar (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2021)
Despite the fact that innovation in the field of hotel business and tourism is the subject of research by many both Kazakhstani and foreign specialists, key issues and growing needs for its regulation remain among the problems that require a comprehensive analysis. Innovations in tourism allow solving a number of problems, associated both with an increase in the level of satisfaction of the cultural needs of the population, and with the creation of conditions for the development of innovative forms of small business, and with the involvement of young people in innovative activities. The purpose of the study is to consider the innovative activities of the hotel business and tourism and identify possible directions for enhancing state policy in this area. Based on the statistical data necessary to build a regression model, the author of the article analyzed the impact of investments in fixed assets in the Republic of Kazakhstan on the volume of services provided by the locations.